Lack of relevant haemogram changes during percutaneous radiotherapy of localised prostate cancer - Zwicker, Felix; Swartman, Benedict; Huber, Peter E.; Herfarth, Klaus; Debus, Jürgen; Hauswald, Henrik (In vivo, 2020)
Background/Aim: In percutaneous radiotherapy dose-distribution and volumetric-load of normal tissue varies in different radiation-techniques. Haematotoxicity may lead to deficiencies of the immune and blood system or to secondary malignancies. Therefore, regular blood-counts are carried out during fractionated radiotherapy. The aim was to investigate patient haemogram courses during radiotherapy of localised prostate-cancer treated with different radiation-techniques (n=3). Patients and Methods: In this prospective study, blood count changes were examined during fractionated radiotherapy (3D-conformal-RT/step-and-shoot-IMRT/helical-IMRT) on the prostate-region in localised prostate-cancer cases (n=50). Results: The whole patient group displayed a small but significant reduction in leukocytes. This reduction was higher in the two IMRT groups compared to the 3D-group but without any case of leukopenia. Haemoglobin- or thrombocyte-levels did not significantly change. Conclusion: Regardless of the delivery mode used, localised fractionated irradiation of prostate region did not cause any clinically relevant haemogram changes in this study. These findings question the necessity of regular blood counts during fractionated radiotherapy of the prostate region for patients without any risk factors.
Gesehen am 28.05.2020